Strategies for dispersion of cariogenic biofilms: applications and mechanisms - Chen, Rourong; Du, Minquan; Liu, Chang (Frontiers in Microbiology, 2022)
Bacteria residing within biofilms are more resistant to drugs than planktonic bacteria. They can thus play a significant role in the onset of chronic infections. Dispersion of biofilms is a promising avenue for the treatment of biofilm-associated diseases, such as dental caries. In this review, we summarize strategies for dispersion of cariogenic biofilms, including biofilm environment, signaling pathways, biological therapies, and nanovehicle-based adjuvant strategies. The mechanisms behind these strategies have been discussed from the components of oral biofilm. In the future, these strategies may provide great opportunities for the clinical treatment of dental diseases. Graphical Abstract